Proceedings of the 21st Annual ACM SIGPLAN Conference on Object-Oriented Programming Systems, Languages, and Applications 2006
DOI: 10.1145/1167473.1167507
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the shape of Java software

Abstract: Large amounts of Java software have been written since the language's escape into unsuspecting software ecology more than ten years ago. Surprisingly little is known about the structure of Java programs in the wild: about the way methods are grouped into classes and then into packages, the way packages relate to each other, or the way inheritance and composition are used to put these programs together. We present the results of the first in-depth study of the structure of Java programs. We have collected a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 20 publications
(22 reference statements)
2
58
0
2
Order By: Relevance
“…Baxter et al [7] looked at the 'shape' of Java Software, finding that certain metrics follow power laws. They later extended their findings in [40] using a large-scale corpus of software, not unlike eariler efforts by Bajracharya et al [5], with both these works serving as pioneering work in studying language design on a larger scale.…”
Section: Related Workmentioning
confidence: 99%
“…Baxter et al [7] looked at the 'shape' of Java Software, finding that certain metrics follow power laws. They later extended their findings in [40] using a large-scale corpus of software, not unlike eariler efforts by Bajracharya et al [5], with both these works serving as pioneering work in studying language design on a larger scale.…”
Section: Related Workmentioning
confidence: 99%
“…Previous similar studies have used a range of tools e.g. purposebuilt bytecode analysis [31], Byte Code Engineering Library [1], Soot Framework [32], Codecrawler [18], and MOOSE [13]. It was noted that Tempero et al's study on inheritance use in Java "had memory limitations that restricted the size of the systems than we could analyse" [32].…”
Section: Study Instrumentationmentioning
confidence: 99%
“…They reported a high correlation between LOC, number of methods (NOM), and out degree of classes. Baxter et al (2006) reported a similar study, however, unlike Wheeldon and Counsell (2003), have observed some metrics that do not follow the power laws. They opined, their use of a more extensive corpus compared to Wheeldon and Counsell (2003) is the reason for the difference.…”
Section: Related Workmentioning
confidence: 75%